2022
DOI: 10.1155/2022/5926049
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Admission Serum Anion Gap and Prognosis of Critically Ill Patients: A Large Multicenter Cohort Study

Abstract: Background. There were controversies over the relationship between Anion gap (AG) and mortality in critically ill patients. Therefore, a large multicenter cohort study was conducted to evaluate the association of AG and mortality in large-scale intensive care units (ICUs) patients. Methods. This retrospective cohort study included adult ICU patients enrolled from eICU Collaborative Research Database. According to initial serum AG upon ICU admission, patients were divided into three groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…AG, as a biomarker for assessing the acid–base of the biotic internal environment, is associated with higher in-hospital mortality in patients presenting with cardiac arrest and sepsis; 7 , 8 with higher ICU and in-hospital mortality in critically ill patients. 9 An elevated level of AG increases all-cause mortality in unselected adults. 10 Moreover, AG can predict short-time prognosis for cerebral infarction patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AG, as a biomarker for assessing the acid–base of the biotic internal environment, is associated with higher in-hospital mortality in patients presenting with cardiac arrest and sepsis; 7 , 8 with higher ICU and in-hospital mortality in critically ill patients. 9 An elevated level of AG increases all-cause mortality in unselected adults. 10 Moreover, AG can predict short-time prognosis for cerebral infarction patients.…”
Section: Discussionmentioning
confidence: 99%
“… 24 There is controversy on the relevance between AG and lactate. Some research found AG was related to lactate, 7 , 9 while some insisted that AG cannot predict hyperlactatemia 25 and the use of AG as an alternative to lactate cannot be recommended. 26 The possible reason results from the various baseline AG levels, albumin levels, clinical setting among individuals, and differences between arterial, venous, and capillary lactate.…”
Section: Discussionmentioning
confidence: 99%
“… 16 AG is commonly used to evaluate acid-base disorders and analyze primary metabolic acidosis. 6 High AG metabolic acidosis is a subcategory of metabolic acidosis, 9 and therefore, AG may be a useful predictor of adverse clinical outcomes in ICU patients. 17 Recent retrospective studies have shown that elevated AG is associated with increased mortality in ICU patients with aortic aneurysm, 7 AKI requiring CRRT, 9 cardiogenic shock, 10 acute pancreatitis 11 and hip fractures.…”
Section: Discussionmentioning
confidence: 99%
“…AG is used to detect acid-base disorders and analyze the primary metabolic acidosis. 6 Recent studies have shown that a high AG level is associated with increased mortality in ICU patients with conditions such as aortic aneurysm, 7 sepsis, 8 acute kidney injury(AKI) requiring continuous renal replacement therapy(CRRT), 9 cardiogenic shock, 10 acute pancreatitis 11 and hip fractures. 12 However, few studies have investigated the association between AG and all-cause mortality in critically ill patients with COPD.…”
Section: Introductionmentioning
confidence: 99%